Tribology Properties on 5W-30 Synthetic Oil with Surfactant and Nanomaterial Oxide Addition - Poppy Puspitasari; Avita Ayu Permanasari; Ayu Warestu; Gilang Putra Pratama Arifiansyah; Diki Dwi Pramono; Timotius Pasang (Universitas Muhammadiyah Magelang, 2023)
This study analyzes the tribological properties of 5W-30 synthetic oil with the addition of surfactants and oxide nanomaterials. This research used SAE 5W-30 lubricant base material with the addition of Aluminum Oxide (Al2O3), Titanium Dioxide (TiO2), and Hybrid Aluminum Oxide (Al2O3) - Titanium Dioxide (TiO2) nanomaterials. The nano lubricants were synthesized using a two-step method by adding nanomaterials by 0.05% volume fraction, followed by 50 ml of 5W-30 synthetic oil and polyvinylpyrrolidone (PVP) surfactant by 0.1%. Then, it was stirred using a magnetic stirrer for 20 minutes, followed by an ultrasonic homogenizer process for 30 minutes. Further, the nanolubricant was tested to identify its thermophysical properties, including density, dynamic viscosity, and sedimentation. It also underwent tribological testing, including wear, coefficient of friction, and surface roughness. Further, the nanomaterial was characterized using SEM, XRD, and FTIR. The morphological analysis using SEM suggested an irregular shape of the Al2O3 nanomaterial surface, while TiO2 has a spherical shape. Besides, phase identification with XRD testing showed corundum and anatase phases. Functional group analysis through the FTIR showedthe presence of Ti-O and Al-O. The highest density and viscosity results without surfactants were obtained in hybrid nanolubricant 779 kg/mm3 and 0.0579 Pa.s, while the use of surfactants resulted in 788.89 kg/mm3 of density and 0.0695 Pa.sviscosity. Tribological gray cast iron FC25 results in the best COF value observed in SAE 5W-30 + PVP-TiO2 lubrication (0.093). The lowest wear mass without surfactant was obtained in the Al2O3-TiO2 nanolubricant hybrid (0.02 grams), the lowest surface roughness in a mixture of PVP and TiO2 surfactants was 0.743 Î¼m. Meanwhile, the surface morphology of gray cast iron FC25 with hybrid nanolubricant SAE 5W-30 (Al2O3-TiO2) and Nanolubricant SAE 5W-30+ (PVP-TiO2) produced the smoothest surface.